2022
DOI: 10.1159/000526444
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Morphologic Changes in MRI during Gastric Balloon Therapy

Abstract: Introduction: Adiposity and excessive weight are on the rise in western industrialized countries. In cases where conservative measures fail and surgical interventions are not (yet) desired, gastric balloon therapy has proven to be a safe and reversible endoscopic method. Methods: Aside from weight progression under gastric balloon therapy and by using MRI, our research paper describes the behavior of different abdominal body fat compartments at the beginning and at the end of the gastric balloon therapy. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(49 reference statements)
0
3
0
4
Order By: Relevance
“…Eighteen studies ( n = 888, I 2 = 0%) 7,41–44,46–49,51–59 evaluated the effect of IGB therapy on BMI. These studies showed a significant reduction, MD: −4.83 [95% CI: −4.31 to −5.36, p < 0.01] (Figure 10A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen studies ( n = 888, I 2 = 0%) 7,41–44,46–49,51–59 evaluated the effect of IGB therapy on BMI. These studies showed a significant reduction, MD: −4.83 [95% CI: −4.31 to −5.36, p < 0.01] (Figure 10A).…”
Section: Resultsmentioning
confidence: 99%
“…41,42 Zerrweck et al 44 compared gastric bypass with pre-operative IGB treatment to gastric bypass alone. The remaining 14 studies were non-comparative observational studies, [46][47][48][49][50][51][52][53][54][55][56][57][58][59] as shown in Tables 3 and 4.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wir haben in einer eigenen Studie die Therapie mittels Magenballon (BIB™ System Intragastric Ballon, apollo endosurgery, Austin, Texas, USA) in Bezug auf die Veränderungen der abdominellen Fettkompartimente, der Muskelmasse anhand eines Markermuskels, und das Volumen der linken Leber mittels MRT untersucht (n = 12) [ 26 ] . In diesen ausgewählten Fällen wurde die Magenballonimplantation als reversible Therapie im Rahmen eines Mehrstufenkonzepts angeboten oder war ausdrücklich gewünscht worden.…”
Section: Wirksamkeit Der Magenballonimplantationunclassified
“…stärkster epigastrischer Schmerzen, die jeweils medikamentös/ konservativ nicht kontrollierbar waren, sowie 1x Verlust des Ballons via naturalis). Allerdings ist unsere Studiengruppe im Vergleich sehr klein [ 26 ] . Stavrou et al diskutierten untersucherbezogene technische Probleme bei der Anwendung des Magenballons als Ursächlich für viele Komplikationen dieser Therapieform [ 40 ] .…”
Section: Verträglichkeit Der Magenballonimplantationunclassified